2008
DOI: 10.1016/j.foodcont.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro tests of suitability of bacteriocin-producing lactic acid bacteria, as potential biopreservation cultures in vacuum-packaged cold-smoked salmon

Abstract: The objectives of this study were to ascertain the in vitro potential of nine bacteriocin-producing lactic acid bacteria (LAB) strains, isolated from vacuum-packaged cold-smoked salmon (CSS), for possible use as biopreservative cultures against Listeria monocytogenes. The antilisterial activity of cultures' supernatants was assessed at 0.5%, 3.0% and 5.0% w/v of salt, at 5°C, 10°C and 25°C both in aerobic and anaerobic atmospheres, simulating the conditions pertaining in vacuum-packaged CSS. The kinetics of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…In kinetic studies, both crude bacteriocins were continuously produced during logarithmic phase followed by optimal production during stationary growth phase, suggesting that these peptides may be secondary metabolites. Similar results were reported for some bacteriocins produced by some LAB isolates [5,64,65] and is contrary for other Lactobacillus species bacteriocins [1,16,25,55,60,66]. Bacteriocin H5 showed a decrease in activity towards the end of stationary growth may be due to proteolytic degration, protein aggregation, and feedback regulation as has been observed for Lactacin ST13BR, Lactacin B, Helveticin J and Enterocin1146 [53,55,67].…”
Section: Discussionsupporting
confidence: 81%
“…In kinetic studies, both crude bacteriocins were continuously produced during logarithmic phase followed by optimal production during stationary growth phase, suggesting that these peptides may be secondary metabolites. Similar results were reported for some bacteriocins produced by some LAB isolates [5,64,65] and is contrary for other Lactobacillus species bacteriocins [1,16,25,55,60,66]. Bacteriocin H5 showed a decrease in activity towards the end of stationary growth may be due to proteolytic degration, protein aggregation, and feedback regulation as has been observed for Lactacin ST13BR, Lactacin B, Helveticin J and Enterocin1146 [53,55,67].…”
Section: Discussionsupporting
confidence: 81%
“…The association of L. casei T3 and L. plantarum PE2 was the most effective, probably due to a competition mechanism against the pathogen. In their study Tomé et al [144] have also selected a strain of Enterococcus faecium among five bacteriocinogenic LAB strains for its ability to induce a decrease of the population of L. innocua inoculated in CSS. However in these studies the inhibition activities were not confirmed on L. monocytogenes.…”
Section: Application Of Lab In Seafoodmentioning
confidence: 99%
“…Enterococci are frequently isolated from various foods of animal origin (Chingwaru et al, 2003;Çitak et al, 2004;Jaffrès et al, 2009;Sergelidis et al, 2010). They have also been isolated from aquatic habitats, fish and seafood (rice et al, 1995;Wilson and Mcafee, 2002;Petersen and Dalsgaard, 2003;Quigg et al, 2009;Al bulushi et al, 2010;Valenzuela et al, 2010).The organisms are also part of the spoilage flora of processed fish products (Dalgaard et al, 2003;Mejlholm et al, 2008;Tomé et al, 2008;Jaffrès et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Enterococci exhibit interesting technological and probiotic properties and their beneficial role in food fermentations, ripening and biopreservation has been recognised (Giraffa, 2003;Hugas et al, 2003;Tomé et al, 2008). Despite their beneficial properties, they are considered to be faecal contamination indicators and responsible for food spoilage (Franz et al, 1999;Dalgaard et al, 2003;Jaffrès et al, 2009).…”
Section: Introductionmentioning
confidence: 99%